Improved PV control that considers charging restrictions of lithium-ion battery - Saeed, Mohammed R.; Imran, Rasool M.; Alwez, Mustafa Abo; Flaih, Firas M. F.; Habib, Habib Ur Rahman (IEEE, 2022)
Lithium-ion battery is one of the most used energy storage technologies in recent times. Enhancing the life span of the Lithium-ion battery is an issue that has technical and economic contributions. This paper addresses improving the life span of Lithium-ion batteries through the appropriate way of charging in the PV system. A modified control methodology is applied for the DC-DC converter-based charger that implements the maximum power point tracking algorithm with considering the battery-safe charging recommendations. The control methodology has been implemented in Matlab Simulink and effectively verified through the simulation results.